Religion and dual-process cognition: a continuum of styles or distinct types?. Issue 2 (2nd April 2016) - Morgan, Jonathan
Abstract : Over the last two decades, various lines of research within cognitive science and social psychology have converged to create dual-process theory. The received view of this theory suggests two distinct cognitive processes: one is intuitive and the other reflective. But the defining features of these two types have been called into question by recent critiques. In response, new constraints have refined the distinctive features of each type, and distinguished between distinct types of processes and differing modes of the same type. This reformulation of dual-process theory bears upon the cognitive science of religion by reorganizing our understanding of religious cognition in relation to these two types of processes. Religious belief has been traditionally associated with type 1, intuitive, processes. This paper reviews the theoretical and empirical literature on dual-process theory and religion in order to suggest that while these basic intuitive processes may support religious beliefs, we must also expand our view to understand belief in relation to varying cognitive modes. These modes exist on a continuum, and are properly understood as type 2, reflective, processes. Thus they present a more nuanced and complex framework for understanding the relationship between varying types of religious belief and cognitive styles.